PENGARUH MARKETING MIX TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN (Studi Kasus: Bisnis Tenun Songket Pandai Sikek) - Rahmat Firdaus; Himyar Pasrizal; Yurma Elsy (Jurnal Manajemen Bisnis Syariah, 2021)
The purpose of this study was to determine how much influence the product, price, place, promotion, service had on purchasing decisions. Using quantitative methods with the t test and f test. The results of the research partially show that there is a significant influence between the product and the purchase decision, there is a significant influence between the price and the purchase decision, there is a significant influence between the place and the purchase decision, there is a significant influence between promotion and purchasing decisions and there is a significant influence between service and purchasing decisions. . Simultaneously, product, price, place, promotion and service have a significant effect on purchasing decisions, product variables, price, place, promotion and service simultaneously or simultaneously affect consumer purchasing decisions. The conclusion that can be drawn from this research is that all the variables tested, namely product, price, place, promotion, and service greatly influence the purchasing decision of the sogke woven product in pandai sikek.